A comparative study of the procedures for medicine approval in the European Union and the United States - Gjeorgiev Blagoj; Miceva Dijana; Karpicarov Dino; Apostolova Paulina; Bogevski Krume; Arev Marija; Gjorgjeska Biljana (Arhiv za farmaciju)
Medicine registration refers to evaluating a medical product's safety, efficacy, and quality, leading to the granting of a Marketing Authorization. Given the intense globalization of the pharmaceutical industry, harmonizing regulatory procedures between the European Medicines Agency (EMA) and the United States's Food and Drug Administration (FDA) is critical for accelerating the availability of new medicines. The EMA oversees three different procedures for medicine registration: Centralized, Decentralized and Mutual Recognition Procedure. Conversely, the FDA offers three registration applications - Investigational New Drug Application, New Drug Application and Abbreviated New Drug Application. A comparison between the FDA and EMA reveals numerous discrepancies within each system and highlights opportunities for harmonization. While both agencies achieve high concordance in their final decisions, the FDA is faster and more streamlined, benefiting from a centralized authority and expedited pathways. The EMA's structured approach ensures thorough evaluations but can delay approvals. Efforts to harmonize procedures, such as the FDA-EMA Parallel Scientific Advice program and the Mutual Recognition Agreement, aim to enhance alignment and reduce development resources, creating a global regulatory environment to streamline the registration of new medicines.